2021
DOI: 10.1186/s12889-021-12025-8
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breastfeeding in rural Western China: does father’s co-residence matter?

Abstract: Background China suffers from a low exclusive breastfeeding rate. Though it has been proofed that paternal support benefits breastfeeding a lot, the correlation between father’s co-residence and exclusive breastfeeding in China remain undiscovered. This study is to provide population-based evidence for the association of paternal co-residence on exclusive breastfeeding in rural western China. We also attempt to detect how the process works by examining the correlation between the father’s co-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Studies proved that the company and support of fathers and families can effectively raise the rate of exclusive breastfeeding and extend the duration of breastfeeding ( 1 , 6 , 34 , 35 ). The nature of work support breastfeeding has a great effect on the improvement of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Studies proved that the company and support of fathers and families can effectively raise the rate of exclusive breastfeeding and extend the duration of breastfeeding ( 1 , 6 , 34 , 35 ). The nature of work support breastfeeding has a great effect on the improvement of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…In southeastern China, lower education levels of grandmothers were associated with decreased rates of breastfeeding [ 14 ]. Furthermore, in rural northwestern China, it was observed that co-residence with the father was correlated with a reduced likelihood of exclusive breastfeeding due to diminished decision-making power regarding breastfeeding practices [ 15 ]. Family members involvement in parenting holds particularly true in western rural China, where the concept of a closely-knit family unit is deeply rooted, often with several generations living under the same roof and sharing parenting responsibilities.…”
Section: Introductionmentioning
confidence: 99%
“…This holds particularly true in western rural China, where the concept of a closely-knit family unit is deeply rooted, often with several generations living under the same roof and sharing child-rearing responsibilities. In this context, fathers are typically not the primary caregivers, as they frequently migrate to cities for work [15]. As a result, grandparents often assume the role of primary caregivers.…”
Section: Introductionmentioning
confidence: 99%